Analysis of the Implementation of Minimum Service Standards at Mersam Community Health Center, Batanghari Regency, Jambi, 2025 - Ayu Nurmala; Ahmad Hafizullah Ritongan; Sri Melda Br. Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
The implementation of Minimum Service Standards (MSS) in the health sector is an obligation of local governments to ensure the provision of basic health services for the community. This study aims to analyze the implementation of MSS at Mersam Community Health Center, Batanghari Regency, in 2025, viewed from the aspects of communication, resources, disposition, and bureaucratic structure, as well as to identify the supporting and inhibiting factors. This research employed a qualitative approach with a descriptive method through interviews, observations, and documentation.The results indicate that the implementation of MSS has been carried out in accordance with existing regulations; however, it has not been fully optimal. The main obstacles include limited health personnel, inadequate facilities and infrastructure, high workload, and low public awareness of preventive services. Supporting factors include leadership commitment and support from the Health Office. The strategies implemented involve improving coordination, optimizing available resources, and strengthening public outreach. The findings emphasize the importance of strengthening resource capacity and enhancing cross-sectoral coordination to ensure that MSS implementation becomes more effective and sustainable in improving the quality of basic health services at the community health center level.